PENGARUH KUALITAS PELAYANAN DAN KERAGAMAN PRODUK TERHADAP KEPUASAN KONSUMEN PADA TOKO KING DI MALANG - yuwana, syamswana (Fakultas Ekonomi dan Bisnis, Universitas 17 Agustus 1945 Surabaya, 2017)
ABSTRAKConsumer satisfaction can be realized well if the company is able to provide quality service and product diversity that consumers expect. The higher the quality of service received then the consumer will be satisfied, so that the consumer will be a permanent consumer in the company. Similarly, the King Shop as a provider of photocopying and stationery products located in Malang are also trying to improve the quality of service and product diversity in accordance with consumer expectations. So the purpose in doing research is to determine the effect of service quality and product diversity to customer satisfaction either simultaneously or partially, to know which influence is most dominant between service quality and product quality to customer satisfaction. The study was conducted at the Poor King Shop. The sample used in this study amounted to 60 respondents. The method used in this sampling is to use probability sampling. Data testing techniques used in this research include the validity test, reliability test with Alpha Cronbach. The method of data analysis used is multiple linear regression analysis to test and prove research hypothesis using computer application program SPSS Version 21. Based on the results of data analysis, the multiple linear regression equation obtained is as follows: Y = 7.446 + 0.207X.1 + 0.482X.2. From multiple linear regression equation can be known variables of service quality and product diversity have an effect on signifikan to consumer satisfaction at king store in malang. Result of t test, have positive and significant effect to consumer satisfaction because t count bigger than t table. Results simultaneously with the F test shows that all independent variables significantly influence customer satisfaction because f count is greater than f table. Therefore H0 is rejected and Ha accepted. The value of multiple determinant coefficient (R Square) of 0.432 indicates that 56.8% of customer satisfaction variables can be explained by independent variables of service quality and product diversity, while the rest of 43.2% is explained by other variables.Â